STRUKTUR KOMUNITAS LARVA TRICHOPTERA DI SUNGAI GARANG SEMARANG - Lila Ris Purdyaningrum; Rully Rahadian; Fuad Muhammad (Jurnal Akademika Biologi, 2013)
River is the natural habitat for macrobiotic organisms, one of them is Trichoptera larvae.      Trichoptera larvae can be used as bio-indicator of water pollution because it is sensitive to environmental and habitat characteristics changes. The objective of this research is to examine the community structure of Trichoptera larvae in Garang River Semarang and the river quality based on the biological and physical-chemical factors. This study used survey method and purposive sampling technique to collect the sample.      The locations of the research are four stations which were determined by the land use around the river. Three samples were taken from each station by using 25 x 40 cm surber net. The findings show that the Trichoptera larvae found in four Garang River Semarang observation stations consisted of five genus; they are Cheumatopsyche, Chimarra, Glossosoma, Hydropsyche, and Tinodes. Relative abundance of Glossosoma and Cheumatopsyche at station I were almost balance, thus there was no dominant genus in the station. Trichoptera larvae dominated station II are Glossosoma and Hydropsyche. The Cheumatopsyche and Chimarra were the dominant genus in station III. While at the station IV, the researcher only found Hydropsyche. Trichoptera larvae which were highly diverse was in station III (H' = 1.41) and the lowest was in station IV    (H' = 0). Trichoptera larvae spread evenly in station I, station II, and station III, while station IV was dominated by genus Hydropsyche. In conclusion, the study showed that the highest density, abundance, and diversity level of the Trichoptera larvae in Garang River was in Tinjomoyo area, which had substrate rocks and fast water currents. Based on biological and physical-chemical factors, the condition of the four observation stations                        in Garang River could be grouped into two categories; not polluted and polluted. Keyword: Community structure, Trichoptera larvae, Garang River